What Stops Unwanted Sexual and Social Advances Made by Heavy Drinking College Men? - Orchowski, Lindsay M. (Journal of interpersonal violence, 2022)
Although rates of sexual aggression are high among college men who engage in heavy drinking, little is known regarding how often heavy drinking college men initiate unwanted sexual advances towards women that could lead to a potential sexual assault or the reasons why these advances stop or proceed. The present study describes heavy drinking college men?s (N = 210) initiation of unwanted sexual and social advances towards women, as well as outcomes of these interactions, including how often these behaviors continue, and men?s perception of what stopped the behavior over a 3-month period. Men indicated whether they were in a situation where a sexual partner noted that she does not want sexual activity to proceed further, initiated unwanted sexual contact, initiated unwanted sexual intercourse, attempted to give a woman alcohol when she did not appear to want to drink, or attempted to take a woman to an isolated location when she did not appear to want to go. These unwanted sexual and social advances most often stopped because of women?s verbal resistance (i.e., saying ?stop? or ?no?), or because men engaged in a discussion regarding the women?s limits or choices. Given that none of the unwanted sexual or social advances stopped because of bystander intervention, the present study highlights the importance of raising awareness of the effectiveness of women?s resistance tactics and continuing to train bystanders to notice and take action to address risky situations.